'It's not hands-on therapy, so it's very limited': Telehealth use and views among allied health clinicians during the coronavirus pandemic. (April 2021) - Malliaras, P.; Merolli, M.; Williams, C.M.; Caneiro, J.P.; Haines, T.; Barton, C.
Abstract: Background: Telehealth services have helped enable continuity of care during the coronavirus pandemic. We aimed to investigate use and views towards telehealth among allied health clinicians treating people with musculoskeletal conditions during the pandemic. Methods: Cross-sectional international survey of allied health clinicians who used telehealth to manage musculoskeletal conditions during the coronavirus pandemic. Questions covered demographics, clinician-related factors (e.g. profession, clinical experience and setting), telehealth use (e.g. proportion of caseload, treatments used), attitudes towards telehealth (Likert scale), and perceived barriers and enablers (open questions). Data were presented descriptively, and an inductive thematic content analysis approach was used for qualitative data, based on the Capability-Opportunity-Motivation Behavioural Model. Results: 827 clinicians participated, mostly physiotherapists (82%) working in Australia (70%). Most (71%, 587/827) reported reduced revenue (mean (SD) 62% (24.7%)) since the pandemic commenced. Median proportion of people seen via telehealth increased from 0% pre (IQR 0 to 1) to 60% during the pandemic (IQR 10 to 100). Most clinicians reported managing common musculoskeletal conditions via telehealth. Less than half (42%) of clinicians surveyed believed telehealth was as effective as face-to-face care. A quarter or less believed patients value telehealth to the same extent (25%), or that they have sufficient telehealth training (21%). Lack of physical contact when working through telehealth was perceived to hamper accurate and effective diagnosis and management. Conclusion: Although telehealth was adopted by allied health clinicians during the coronavirus pandemic, we identified barriers that may limit continued telehealth use among allied health clinicians beyond the current pandemic. Highlights: Allied health clinicians rapidly adopted telehealth during the coronavirus pandemic. They view telehealth as part of their clinical role. However, most felt they lacked adequate training to deliver telehealth services. And that telehealth is inferior to face-to-face care and undervalued by patients. These barriers may limit use of telehealth beyond the pandemic.